Water and trehalose: how much do they interact with each other? - Pagnotta, SE; McLain, SE; Soper, A; Bruni, F; Ricci, M (American Chemical Society, 2010)
The observation made by early naturalists that some organisms could tolerate extreme environmental condisions and "enjoy the advantage of real resurrection after death" [ Spallanzani , M. Opuscules de Physique Animale et Vegetale 1776 (translated from Italian by Senebier , J. Opuscules de Physique Animale et Vegetale 1787 , 2 , 203 - 285 )] stimulated research that still continues to this day. Cryptobiosis, the ability of an organism to tolerate adverse environments, such as dehydration and low temperatures, still represents an unsolved and fascinating problem. It has been shown that many sugars play an important role as bioprotectant agents, and among the best performers is the disaccharide trehalose. The current hypothesis links the efficiency of its protective role to strong modifications of the tetrahedral arrangement of water molecules in the sugar hydration shell, with trehalose forming many hydrogen bonds with the solvent. Here, we show, by means of state-of-the-art neutron diffraction experiments combined with EPSR simulations, that trehalose solvation induces very minor modifications of the water structure. Moreover, the number of water molecules hydrogen-bonded to the sugar is surprisingly small.